1994
DOI: 10.3109/10731199409138816
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Gas Trapping Differences Among Animal Species in Response to Intravenous Infusion of Perfluorocarbon Emulsions

Abstract: In animals, increased lung volume and a concomitant failure of lungs to collapse normally upon autopsy can occur following intravenous injection of higher vapor pressure perfluorocarbons (PFCs) administered as emulsions. Responses vary considerably depending on the PFC, dose and animal model. The study objective was to examine animal species differences with respect to this apparent pulmonary gas trapping (PGT) phenomenon which has not been observed in human clinical trials. A dose-related increase in postmort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Compared to rabbits, dogs have been found to be less sensitive to the higher dosage of PFC emulsion (up to 12 mL/kg) (Leakakos et al 1994). It has been reported that several important factors, such as the number of pulmonary intravascular macrophages, collateral ventilation, transpulmonary pressure and the airway geometry may contribute to these species-related responses (Leakakos et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to rabbits, dogs have been found to be less sensitive to the higher dosage of PFC emulsion (up to 12 mL/kg) (Leakakos et al 1994). It has been reported that several important factors, such as the number of pulmonary intravascular macrophages, collateral ventilation, transpulmonary pressure and the airway geometry may contribute to these species-related responses (Leakakos et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that several important factors, such as the number of pulmonary intravascular macrophages, collateral ventilation, transpulmonary pressure and the airway geometry may contribute to these species-related responses (Leakakos et al 1994). As indicated in arterial blood samples, respiratory acidosis was observed in both the IV and transcutaneous experiments as a result of repeated droplet injections.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the apparatus for measuring ELGV is much less expensive (hundreds of dollars) than the equipment for noninvasive or invasive pulmonary function measurements (tens of thousands of dollars) in small laboratory animals. Finally, investigators from academic [28,38,39], government [40], and pharmaceutical [27,41,42] laboratories have used the ELGV measurement to advance their research. Thus, I believe the ELGV measurement is a costeffective alternative approach for assessing in vivo airway mechanics in small laboratory animals and for examining novel therapies for treating human lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lung retention of microbubbles within the pulmonary microvasculature is a size‐dependent phenomenon . The formulation of transpulmonary, micron‐sized emulsions can minimize certain types of PFC‐related bioeffects . Additionally, the pharmacokinetics of sonosensitive PFC particles are directly related to the time window between vascular administration of the particles and the application of ultrasound to activate the particles.…”
Section: Introductionmentioning
confidence: 99%